FRI0338 SIMILAR CARDIOVASCULAR COMORBIDITY AND HIGHER DEPRESSION RATES IN PSORIATIC ARTHRITIS COMPARED TO AGE- AND SEX-MATCHED RHEUMATOID ARTHRITIS AND DIABETES MELLITUS PATIENTS. (2nd June 2020) - Fragoulis, G. E.; Evangelatos, G.; Tentolouris, N.; Fragkiadaki, K.; Panopoulos, S.; Konstantonis, G.; Iliopoulos, A.; Chatzidionysiou, K.; Sfikakis, P.; Tektonidou, M.
Abstract : Background: Comorbidities are frequent in psoriatic arthritis (PsA) but it is not known how they differ from other high comorbidity burden diseases like rheumatoid arthritis (RA) and diabetes mellitus (DM). Objectives: To compare the prevalence of comorbidities in PsA vs. RA and DM patients. Methods: 215 PsA patients were age/gender-matched with 215 RA and 215 DM patients from two tertiary hospitals. Prevalence of comorbidities (hypertension, current smoking, hyperlipidemia, obesity (BMI≥30), coronary disease [CD], stroke, MACE [combined CD and stroke], depression, osteoporosis, history of malignancies) were compared across the three groups. Within PsA group, associations between comorbidities and demographic and clinical features (e.g entheitis), including PsA phenotypes (RA-like vs oligoarthritis pattern and Axial-involvment vs Non-Axial-involvement) were assessed. Results: Hyperlipidaemia, obesity and depression were more frequent in PsA vs. RA. Depression and osteoporosis were more common in PsA vs DM. In contrast, hypertension was more frequent in DM. All other comorbidities, including frequency of stroke, CD and major adverse cardiovascular events did not differ between groups. Results remain unchanged after adjustments (Table 1 ). Within PsA group, depression was associated with female gender (p=0.02), older age (p=0.03), higher disease duration (p=0.04) and current smoking (p=0.04). MACEs in PsA, were associated with male gender (p=0.03), older age (p=0.0002), dyslipidaemia (p=0.003) and hypertension (p<0.0001). No differences were found between different phenotypes of PsA. Conclusion: PsA patients had higher BMI and hyperlipidaemia compared to RA but not to DM. MACE is comparable between PsA and RA or DM, while depression is more common in PsA. Taking into account certain risk factors, screening for and management of comorbidities in PsA is important in the clinical setting. Disclosure of Interests: George E. Fragoulis: None declared, Gerasimos Evangelatos: None declared, Nikolaos Tentolouris: None declared, Kalliopi Fragkiadaki: None declared, Stylianos Panopoulos: None declared, George Konstantonis: None declared, Alexios Iliopoulos: None declared, Katerina Chatzidionysiou Consultant of: AbbVie, Pfizer, Lilly., Petros Sfikakis Grant/research support from: Grant/research support from Abvie, Novartis, MSD, Actelion, Amgen, Pfizer, Janssen Pharmaceutical, UCB, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer